Mapping Indonesia’s South-South Triangular Cooperation Initiatives & potential: Climate Adaptation and Mitigation - Adjani, Wulan Kencana (Institute of International Studies, 2023)
Indonesia has committed to the ASEAN Outlook on the Indo-Pacific (AOIP), and one of the commitments includes its efforts to enhance South-South Cooperation (SSC). Within those SSC sectors, one of the most promising sectors are the Climate change aspects such as Agriculture, disaster risk reduction, renewable energy and energy efficiency, forestry, transport, water resources, and waste management. Notably, countries' recognition is growing to utilize SSC as a strategic tool in addressing climate change and achieving their National Development Contributions (NDC). This paper employs qualitative research methods, drawing insights from existing literature and data, to analyse Indonesia's SSC efforts as part of its AOIP commitment. The study sheds light on Indonesia's endeavours to provide SSC within the Indo-Pacific region, considering the political, economic, and strategic benefits of assisting countries in this area. Additionally, it underscores the significance of technological exchange, particularly with countries sharing similar geo-climatic, cultural, and socio-economic conditions, in fostering effective cooperation, particularly within the Climate Change agenda. The study proposes a potential framework for cooperation by aligning each host country's specific needs with an analysis of their NDCs, complemented by the expertise of contributing nations.